Validity of A-Mode ultrasound for estimating body fat percentage of young adult athletes: A multicomponent model study - Wagner, D. R.; Cafferty, E. A.; Haper, S. A.; Vala, M. N. (Medicine & Science in Sports & Exercise, 2025)
Body fat percentage (%BF) estimated from subcutaneous fat thickness measured by A-mode ultrasound (%BFUS) has been compared with %BF estimates from laboratory methods such as dual-energy x-ray absorptiometry (DXA) and air displacement plethysmography (ADP); however, comparison to a four-component (4C) reference model is lacking.